LIM protein Ajuba promotes liver cell proliferation through its involvement in DNA replication and DNA damage control. Issue 14 (15th June 2022) - Dommann, Noëlle; Gavini, Jacopo; Sánchez‐Taltavull, Daniel; Baier, Felix Alexander; Birrer, Fabienne; Loforese, Giulio; Candinas, Daniel; Stroka, Deborah
Abstract : The LIM‐domain protein Ajuba is associated with cell proliferation, a fundamental process of tissue regeneration and cancer. We report that in the liver, Ajuba expression is increased during regeneration and in tumour cells and tissues. Knockout of Ajuba using CRISPR/Cas9 is embryonic lethal in mice. shRNA targeting of Ajuba reduces cell proliferation, delays cell entry into S‐phase, reduces cell survival and tumour growth in vivo and increases expression of the DNA damage marker γH2AX. Ajuba binding partners include proteins involved in DNA replication and damage, such as SKP2, MCM2, MCM7 and RPA70. Taken together, our data support that Ajuba promotes liver cell proliferation associated with development, regeneration and tumour growth and is involved in DNA replication and damage repair. Abstract : Ajuba is highly expressed in proliferating liver cells, such as during regeneration and in liver cancer cells and tissues. Cells with knocked‐down Ajuba show decreased proliferation, delayed entry into S‐Phase, reduced cell survival and tumour growth and increased expression of the DNA damage marker γH2AX. Ajuba appears to be involved in DNA replication and DNA damage repair in the liver.